From Theory to Practice: Translating Whole-Genome Sequencing (WGS) into the Clinic. Issue 12 (December 2018) - Balloux, Francois; Brønstad Brynildsrud, Ola; van Dorp, Lucy; Shaw, Liam P.; Chen, Hongbin; Harris, Kathryn A.; Wang, Hui; Eldholm, Vegard
Abstract : Hospitals worldwide are facing an increasing incidence of hard-to-treat infections. Limiting infections and providing patients with optimal drug regimens require timely strain identification as well as virulence and drug-resistance profiling. Additionally, prophylactic interventions based on the identification of environmental sources of recurrent infections (e.g., contaminated sinks) and reconstruction of transmission chains (i.e., who infected whom) could help to reduce the incidence of nosocomial infections. WGS could hold the key to solving these issues. However, uptake in the clinic has been slow. Some major scientific and logistical challenges need to be solved before WGS fulfils its potential in clinical microbial diagnostics. In this review we identify major bottlenecks that need to be resolved for WGS to routinely inform clinical intervention and discuss possible solutions. Highlights: In principle, WGS can provide highly relevant information for clinical microbiology in near-real-time, from phenotype testing to tracking outbreaks. However, despite this promise, the uptake of WGS in the clinic has been limited to date, and future implementation is likely to be a slow process. The increasing information provided by WGS can cause conflict with traditional microbiological concepts and typing schemes. Decreasing raw sequencing costs have not translated into decreasing total costs for bacterial genomes, which have stabilised. Existing research pipelines are not suitable for the clinic, and bespoke clinical pipelines should be developed.